PENGARUH PENGOLAHAN TANAH DAN PEMBERIAN MULSA ORGANIK TERHADAP PERUBAHAN BEBERAPA SIFAT KIMIA TANAH PSAMMENT DAN HASIL JAGUNG MANIS (Zea mays Saccharata Sturt) - Ruhaimah Ruhaimah; Herviyanti Herviyanti; Adrinal Adrinal; Giska Oktabriana (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
A research about effect of soil managment and organic mulch application on soil physical properties of psamment and conr production was conducted in Korong Muaro, Nagari Sunur Kecamatan Nan Sabaris Kabupaten Padang Pariaman, as well as in soil laboratory, Agriculture Faculty, Andalas University Padang. This research was done from April – October 2009. The objective of the research was to identify interaction effect between soil cultivation and organic mulch application on chemical properties of psamment and production of sweet corn. This research was designed in two factors: 3 x 4 with three replications. The first factor was soil cultivation which consisted of 3 levels (Po = No-till, P1 = Minimum tillage, P2 = Conventional till). The second factor was organic mulch application, which consisted of four levels: Z = without mulch addition, T = Titonia for 8 ton DW/ha, K = Chromolaena for 8 ton DW/ha, J = straw 8 ton DW/ha. The result showed that soil cultivation combined with rice straw mulch application could increase N, P, K elements in soil. Soil N content increased from 0,17 % to 0,28 %, avail-P from 52,57 ppm to 88,60 ppm, and K-exch from 0,64 me/100g to 2,35 me/100g, however, minimum tillage gave the highest yield which was 7,68 ton weight of corn seeds + the stalk /hektar, and rice straw mulch showed the highest among the organic mulch applied, which was 8,85 ton/ha.Keywords: Soil cultivation, organic mulch, psamment, sweet corn